State Physicians Bleeding John Bull to Death!! - Cruikshank, George, 1792-1878 [after?] (Le Petit, 1816)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons; John Bull (Symbolic character); War, Cost of